Thrombosis in Psoriasis: Cutaneous Cytokine Production as a Potential Driving Force of Haemostatic Dysregulation and Subsequent Cardiovascular Risk - Visser, Maria J. E.; Tarr, Gareth; Pretorius, Etheresia (Frontiers in Immunology, 2021)
Psoriasis (PsO) is a common T cell-mediated inflammatory disorder of the skin with an estimated prevalence of 2%. The condition manifests most commonly as erythematous plaques covered with scales. The aetiology of PsO is multifactorial and disease initiation involves interactions between environmental factors, susceptibility genes, and innate and adaptive immune responses. The underlying pathology are mainly driven by interleukin-17. In addition, various inflammatory mediators from specific T helper (TH) cell subsets, namely TH1, TH17, and TH22, are overexpressed in cutaneous lesions and may also be detected in the peripheral blood of psoriatic patients. Moreover, these individuals are also at greater risk, compared to the general population, of developing multiple comorbid conditions. Cardiovascular disease (CVD) has been recognised as a prominent comorbidity of PsO. A potential mechanism contributing to this association may be the presence of a hypercoagulable state in these individuals. Inflammation and coagulation are closely related. The presence of chronic, low-grade systemic inflammation may promote thrombosis – one of the major determinants of CVD. A pro-inflammatory milieu may also induce the expression of tissue factor, augment platelet activity, and perturb the vascular endothelium. Altogether, these changes will result in a prothrombotic state. In this review, we describe the aetiology of PsO, as well as the pathophysiology of the condition. We also consider its relationship to CVD. Given the systemic inflammatory nature of PsO, we evaluate the potential contribution of prominent inflammatory mediators (implicated in PsO pathogenesis) to establishing a prothrombotic state in psoriatic patients